Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/adma.201301494
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Polymer Solar Cells Based on Benzothiadiazole and Alkylphenyl Substituted Benzodithiophene with a Power Conversion Efficiency over 8%

Abstract: A new copolymer PBDTP-DTBT based on benzothiadiazole and alkylphenyl substituted benzodithiophene is synthesized and characterized. The correlation of the evolution of the morphology and photovoltaic performance is investigated. The power conversion efficiency of the polymer solar cells based on PBDTP-DTBT/PC71 BM (1:1.5, w/w) reaches up to 8.07%, under the irradiation of AM 1.5G, 100 mW/cm(2) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
229
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(232 citation statements)
references
References 61 publications
3
229
0
Order By: Relevance
“…[1][2][3][4] Much remains nevertheless to be learned about how light is converted to charges and subsequent current in those devices. Typically, an electrondonating conjugated polymer is blended with an electronaccepting fullerene in the photovoltaic active layer, spontaneously forming an interpenetrating network known as the bulk heterojunction (BHJ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Much remains nevertheless to be learned about how light is converted to charges and subsequent current in those devices. Typically, an electrondonating conjugated polymer is blended with an electronaccepting fullerene in the photovoltaic active layer, spontaneously forming an interpenetrating network known as the bulk heterojunction (BHJ).…”
Section: Introductionmentioning
confidence: 99%
“…The samples were excited with an excess energy ranging from 0.1 to 1.4 eV compared to the 1.8 eV polymer absorption edge. We have previously found that extremely low excitation fluence (<4 μJ/ cm 2 ) is necessary to avoid laser-induced exciton annihilation and charge recombination artifacts for PBDTTPD-based samples. 7 With an even improved experimental sensitivity, we have now carefully recorded all data below this threshold and verified that the dynamics for each measurement are fluence-independent in this regime.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Significant improvements have been achieved in understanding the correlations between polymer structure and photovoltaic performance, which have helped to boost the power conversion efficiency (PCE) over 7% in several well-known backbones, such as benzodithiophene (BDT) and thienothiophene (TT) (PBDT-TT) [15][16][17][18][19][20][21][22][23][24][25][26][27][28], BDT and benzothiadiazole (BT) (PBDT-BT) [29,30], BDT and thienopyrroledione (TPD) (PBDT-TPD) [31], etc.…”
Section: Introductionmentioning
confidence: 99%